2016
DOI: 10.1142/s0219876216410012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Violent Impinging Jet Flows with Improved SPH Method

Abstract: This paper presents an implementation of an improved smoothed particle hydrodynamics (SPH) method for simulating violent water impinging jet flow problems. The presented SPH method involves three major modifications on the traditional SPH method, (1) The kernel gradient correction (KGC) and density correction are used to improve the computational accuracy and obtain smoothed pressure field, (2) a coupled dynamic solid boundary treatment (SBT) is used to remove the numerical oscillation near the solid boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Kernel gradient correction was developed to improve the simulation accuracy, and Bonet and Lok (1999) proved that by theoretical derivation. Shao et al (2012) and Zhang and Liu (2017) have applied KGC in SPH simulation of liquid sloshing dynamics, high velocity impact, and violent impinging flow problems (Shao et al, 2016), which all focus on singlephase flow problems. Zhu et al (2018) presented a SPH model for simulating multiphase flows with the use of KGC.…”
Section: Kernel Gradient Correctionmentioning
confidence: 99%
“…Kernel gradient correction was developed to improve the simulation accuracy, and Bonet and Lok (1999) proved that by theoretical derivation. Shao et al (2012) and Zhang and Liu (2017) have applied KGC in SPH simulation of liquid sloshing dynamics, high velocity impact, and violent impinging flow problems (Shao et al, 2016), which all focus on singlephase flow problems. Zhu et al (2018) presented a SPH model for simulating multiphase flows with the use of KGC.…”
Section: Kernel Gradient Correctionmentioning
confidence: 99%
“…Hence, an SPH approximation scheme, which is of higher order accuracy and is insensitive to disordered particle distribution, is necessary for modeling HVI. In this paper, the KGC technique [Shao et al (2012a[Shao et al ( , 2016 Liu et al (2017)], which mathematically improves the accuracy of the gradient of the kernel functions (or kernel gradient), is extended from 2D to 3D, and from modeling incompressible flows to HVI problems. In the KGC technique, a modified or corrected kernel gradient is obtained by multiplying the original kernel gradient with a local reversible matrix L(r i ).…”
Section: Kgc Techniquementioning
confidence: 99%
“…Through numerical simulation, the reason for a scale effect of the impact pressure was elucidated. Shao et al [19] improved the traditional smoothed particle hydrodynamics (SPH) method and verified its effectiveness by simulating the water jet impingement problem. The results showed that the improved SPH method can accurately simulate the shape and pressure distribution of an impinging jet.…”
Section: Introductionmentioning
confidence: 99%